2019
DOI: 10.1111/cch.12716
|View full text |Cite
|
Sign up to set email alerts
|

Empowerment in families raising a child with cerebral palsy during early childhood: Associations with child, family, and service characteristics

Abstract: BackgroundInsight into family empowerment is important in order to develop and offer services that support and strengthen parents caring for a child with disability. The aims of this study were to describe empowerment trajectories among parents caring for a young child with cerebral palsy (CP) and to explore associations between parental empowerment and characteristics of the child and family and the services they receive.Methods58 children (median age at first assessment 28 months, range 12–57) and their pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 34 publications
0
26
0
1
Order By: Relevance
“…One explanation for this finding is that children who are GMFCS Levels IV or V have the most complex needs (Palisano et al, 2010) and these families may have the least amount of resources for advocacy as a result. In contrast, Kalleson et al (2019) found that empowerment was lower within the community/political environment in families of children who are GMFCS Levels II or III compared with those who are GMFCS Levels IV or IV. In addition, our families reported higher levels of empowerment in all subscales of the FES compared with Kalleson et al who reported a mean of 2.4 for the community/political subscale compared with our mean of 2.9.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…One explanation for this finding is that children who are GMFCS Levels IV or V have the most complex needs (Palisano et al, 2010) and these families may have the least amount of resources for advocacy as a result. In contrast, Kalleson et al (2019) found that empowerment was lower within the community/political environment in families of children who are GMFCS Levels II or III compared with those who are GMFCS Levels IV or IV. In addition, our families reported higher levels of empowerment in all subscales of the FES compared with Kalleson et al who reported a mean of 2.4 for the community/political subscale compared with our mean of 2.9.…”
Section: Discussionmentioning
confidence: 90%
“…Significant relationships were found between the FES family subscale and GMFM‐66, GMFM Dimension B sitting and GMFM Dimension D standing, but not with GMFM Dimension C crawling and kneeling and GMFM Dimension E walking, running and jumping. Interestingly, Kalleson et al (2019) also reported no differences in the FES family subscale in children with CP grouped by GMFCS level. Although not the same as family empowerment, differences in family ecology with regard to family expectations, expected achievement and levels of control were reported to vary by GMFCS level in a large study of children with CP by LaForme et al (2014).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations